Iron Chelation Therapy with Deferasirox Results in Improvement of Liver Enzyme Level in Patients with Iron Overload-Associated Liver Dysfunction - Yasuo Miura; Yusuke Matsui; Hitomi Kaneko; Mitsumasa Watanabe; Mitsuru Tsudo (Case Reports in Medicine)
Iron chelation therapy (ICT) has been applied for the patients with iron overload-associated liver dysfunction since it is one of the causes of death in patients with intractable hematological diseases requiring multiple red blood cell transfusions. Recently, deferasirox (DSX), a novel, once-daily oral iron chelator, was demonstrated to have similar efficacy to the conventional continuous infusion of deferoxamine on a decrease in serum ferritin (SF) level in heavily transfused patients. We show three cases of transfusion-mediated iron-overloaded patients with an elevated serum alanine aminotransaminase (ALT). All three patients who received the ICT with DSX showed a decrease in ALT level in association with a decrease in SF level. It is suggested that DSX therapy could be considered to expect the improvement of liver damage for iron-overloaded patients with an abnormal ALT level.